Reuse of effluent from dyeing process of polyamide fibers modified by double barrier discharge (DBD) plasma. Issue 6 (1st February 2016) - Oliveira, Fernando Ribeiro; Steffens, Fernanda; Souto, Antonio Pedro; Zille, Andrea
Abstract: Low-temperature plasma technology becomes more and more attractive compared with traditional wet processes in textile preparation and finishing due to its high efficiency and low environmental impact. The objective of this study was to investigate the influence of dielectric barrier discharge plasma treatment on the trichromic dyeing process of polyamide 6.6 (PA66) and the reuse of the generated effluents for new dyeing processes. Chemical and physical characterization of the plasma-treated polyamide fibers was studied by means of static and dynamic contact angle, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy micrographs, and atomic force microscopy (AFM). Plasma treatment greatly increases the hydrophilicity and adhesion of PA66, due to the increase of polar groups and roughness on the fibers surface as confirmed by XPS and AFM. The kinetics of dyeing is quicker but leveled with high rubbing, light, and washing fastness quality. The reuse of the effluent obtained after dyeing of the plasma-treated fabrics showed excellent results of reproducibility, uniformity, and washing fastness. It was possible to reproduce the standard color for three dyeing cycles using the same effluent reducing the effluent load with a significant diminution in costs and environmental impact.